Feature guidance by negative attentional templates depends on search difficulty. Issue 3 (21st April 2019) - Conci, Markus; Deichsel, Cassandra; Müller, Hermann J.; Töllner, Thomas
ABSTRACT: Prior knowledge about an upcoming target can bias attention and facilitate visual search performance. However, whether knowledge about distractors can likewise enhance search, biasing attention away from to-be-avoided items, is less clear. Here, we investigated whether the utilization of such attentional templates is affected by search difficulty. Results from two experiments revealed search efficiency to be reliably increased when positive cues provide information about the upcoming target (relative to neutral, baseline cues) irrespective of whether search was easy (low target-nontarget similarity) or difficult (high target-nontarget similarity). By contrast, negative cues that inform about a to-be-avoided distractor were found to facilitate performance only during difficult (but not easy) search, that is, when responses were relatively slow. This suggests that, contrary to positive target templates, negative distractor templates can be used effectively only when the search task is difficult, which provides sufficient time for processes of distractor inhibition to operate.